Accuracy of a 7-item patient-reported stand-alone tool for periodontitis screening - Sekundo, Caroline; Bölk, Tobias; Kalmus, Olivier; Listl, Stefan (Journal of Clinical Medicine, 2021)
Periodontitis is interrelated with various other chronic diseases. Recent evidence suggests that treatment of periodontitis improves glycemic control in diabetes patients and reduces the costs of diabetes treatment. So far, however, screening for periodontitis in non-dental settings has been complicated by a lack of easily applicable and reliable screening tools which can be applied by non-dental professionals. The purpose of this study was to assess the diagnostic accuracy of a short seven-item tool developed by the German Society for Periodontology (DG PARO) to screen for periodontitis by means of patient-reported information. A total of 88 adult patients filled in the patient-reported Periodontitis Risk Score (pPRS; range: 0 points = lowest periodontitis risk; 20 points = very high periodontitis risk) questionnaire before dental check-up at Heidelberg University Hospital. Subsequent clinical assessments according to Periodontal Screening and Recording (PSR®) were compared with pPRS scores. The diagnostic accuracy of pPRS at different cutoff values was assessed according to sensitivity, specificity, positive, and negative predictive values, as well as Receiver-Operator-Characteristic curves, Area Under the Curve (AUC), and logistic regression analysis. According to combined specificity and sensitivity (AUC = 0.86; 95%-CI: 0.76–0.95), the diagnostic accuracy of the pPRS for detecting periodontal inflammation (PSR® ≥ 3) was highest for a pPRS cutoff distinguishing between pPRS scores < 7 vs. ≥ 7. Patients with pPRS scores ≥ 7 had a 36.09 (95%-CI: 9.82–132.61) times higher chance of having a PSR® ≥ 3 than patients with scores < 7. In conclusion, the pPRS may be considered an appropriately accurate stand-alone tool for the screening for periodontitis.
Gesehen am 23.02.2021